Enhancing the Development of Audiation in Early Music Education Using Multimedia (a Polish Example) - Ewa Parkita; Pawel A. Trzos (Pensa MultiMedia, 2017)
This article refers to the use of multimedia on early stages of music education in the context of the category of audiation. Theory of universal music learning, according to Gordon, is mostly directed at teachers. The text presents the possibility of implementing E. E. Gordon's theory into professional training of early music education teachers at Kazi - mierz Wielki University in Bydgoszcz in Poland. The author recognises the importance of shaping research competences of future teachers as they help students use not only practical (pedagogical), but empirical work of E. E. Gordon's theory. The text presents also the reports from research on the application of E. E. Gordon's Theory of Music Learning, carried out by students of early school and music education at Kazimierz Wielki University in Bydgoszcz in Poland. Such expectations are taken into consideration in the Music Fairytale "e-Audiation Songbook" project, described in this text, which from the beginning has been the field of practical and empirical application of the elements of E.E. Gordon's theory by the staff and student team cooperating in the Faculty of Music Education of the Kazimierz Wielki University in Bydgoszcz.